Efficacy of prophylactic dexamethasone on postoperative nausea and vomiting in laparoscopic appendicectomy: a randomized controlled trial / Ng Shin Ann ... [et al.] - Ng, Shin Ann; Seevaunnamtum, S Praveena; Hassan, Mohamad Hasyizan; Mazlan, Mohd Zulfakar; Che Omar, Sanihah (Faculty of Medicine, 2025)
Introduction: Dexamethasone has been established as an ef f ective prophylactic antiemetic in various studies done in elective surgery. However, its ef f icacy in emergency surgery specif ically, laparoscopic appendicectomy is not well documented. This study was conducted to compare the ef f icacy of prophylactic intravenous (IV) dexamethasone 8mg in preventing postoperative nausea and vomiting (PONV) in this surgical population. Methods: A total of 84 participants were recruited f or the study in Hospital Universiti Sains Malaysia and were randomly assigned in equal numbers to treatment group with prophylactic IV dexamethasone 8mg or placebo. The outcomes of both groups were taken at three-time intervals; f irst hour, 12 th hour and 24 th hour postoperatively which were proportion of PONV, PONV scores, pain scores and the need f or rescue antiemetic. Results: The group receiving dexamethasone had significantly lower proportion of PONV compared to control group in the first hour postoperatively (dexamethasone vs Control; 16.7% vs 42.9%, P = 0.009) and at 24 hour postoperatively (0% vs 14.3%, P = 0.011). The dexamethasone group also required less rescue antiemetic at the f irst hour (14.3% vs 35.7%, P = 0.023) and 12 th hour postoperatively (0% vs 11.9%, P = 0.021). No signif icant dif ferences in pain scores or PONV scores were found in both groups. Conclusion: Prophylactic dexamethasone reduced postoperative nausea and vomiting (PONV) incidence in the f irst hour and 24 hours post-surgery, decreased the need f or rescue antiemetics in the f irst hour and 12th hour, but did not signif icantly affect analgesia or PONV severity between groups. th